Privatization and nationalization cycles - Chang, Roberto (NBER working paper series, 2009)
"This paper studies the cycles of nationalization and privatization in resource-rich economies. We discuss available evidence on the drivers and consequences of privatization and nationalization, review the existing literature, and present illustrative case studies. Our main contribution is then to develop a static and dynamic model of the choice between private and national regimes for the ownership of natural resources. In the model, this choice is driven by a basic equality-efficiency tradeoff: national ownership results in more redistribution of income and more equality, but undermines incentives for effort. The resolution of the tradeoff depends on external and domestic conditions that affect the value of social welfare under each regime. This allows us to characterize how external variables - such as the commodity price - and domestic ones - such as the tax system - affect the choice of private vs. national regimes. The analysis therefore identifies the determinants of the observed cycles of privatization and nationalization, and is consistent with a variety of observed phenomena"--National Bureau of Economic Research web site